THE PHENOMENON OF POLYSEMY AS A PHENOMENON OF LINGUISTICS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article discusses the phenomenon of polysemy and the lexicological difficulties associated with it. In order to investigate the phenomenon of polysemy, it is necessary to complex definition of this phenomenon. Polysemantic words are analyzed in detail, which have both direct and figurative meaning, as well as tropes - metaphor and metonymy as a means of displaying polysemy. An important role is assigned to the context in the translation and understanding of polysemantic words.